POLA ASUH ORANG TUA PADA ANAK BERKEBUTUHAN KHUSUS AUTISME DIRUMAH PINTAR SALATIGA - Wijayanti, Mala Nur; Windrawanto, Yustinus; Septiningtyas, Maya Rahadian (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research was conducted at Rumah Pintar Salatiga. The study aims to determine how the parenting pattern of parents to children with special needs autism. This type of research is qualitative with a case study technique with a focus on parents who have children with special needs autism. The data analysis technique uses Pattern Matching data analysis, and the data collection techniques used are interviews and observations. The results of the interviews that have been conducted, parents who have children with autism apply permissive and authoritative parenting patterns. The conclusion of this study is that parents with authoritative parenting patterns will give children freedom while still providing direction and supervision to children, while parents with permissive parenting patterns provide freedom without supervision and assertiveness to children.